Gravitational waves in a quantum electrodynamic perspective - Avramenko, Aleksandr G. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
Resent scientific progress has suggested that gravitational waves can, under certain conditions, be reflected in a similar manner to electromagnetic waves. As a consequence, it is necessary for scientists to begin incorporating the theories of electromagnetic wave optics unto gravitational waves in order to better understand their physical behavior. This manuscript attempts to extrapolate the behavior of a gravitational wave trapped in a Fabry–Pérot cavity by utilizing theories used to model an electromagnetic wave trapped under similar conditions. Using classical optical theories, it is determined that a pair of microscopic black holes with a mass of ~7.38 × 1014 kg separated by a distance of 1 micron would generate a gravitation wave of approximately 100 GHz. Moreover, the shortcomings of classical theories of gravity are discussed as they are applied to microscopic scales.
Optica Applicata, Vol. 54, 2024, nr 3, s. 327-336
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; electrodynamics; gravity; quantum; cavity; optical resonator